แนวทางการพัฒนาพื้นที่สวนสาธารณะเขตสายไหม กรุงเทพมหานคร (Guidelines to Develop Public Park Areas in Sai Mai District, Bangkok) - เดชะชาติ, นนทพจน์; คงอ้วน, วราลักษณ์ (Asian Creative Architecture, Art and Design, 2014)
บทคัดย่อ บทความวิจัยนี้มีวัตถุประสงค์ คือ 1) ศึกษาสถานการณ์สวนสาธารณะในเขตสายไหม 2) จัดทำบัญชีสวนสาธารณะในเขตสายไหม กรุงเทพมหานคร 3) วิเคราะห์ความคิดเห็นของประชาชนที่มีต่อการพัฒนาพื้นที่สวนสาธารณะ และ 4) เสนอแนะแนวทางการพัฒนาพื้นที่สวนสาธารณะที่มีความสอดคล้องกับความต้องการของประชาชนในพื้นที่ ผลการวิจัยพบว่า เขตสายไหมมีสวนสาธารณะที่ประชาชนเข้าไปทำกิจกรรมได้จริง 2 ประเภท ได้แก่ สวนชุมชนและสวนหมู่บ้าน คิดเป็นอัตราส่วนพื้นที่สวนสาธารณะต่อประชากรได้เท่ากับ 3 ตารางเมตรต่อคน ประชาชนส่วนใหญ่มีความต้องการระดับมากในเรื่องการปรับปรุงพื้นที่รกร้างให้กลายเป็นสวนสาธารณะ การปรับปรุงและดูแลสวนสาธารณะที่มีอยู่เดิมอย่างสม่ำเสมอ รวมถึงการเพิ่มเติมสิ่งอำนวยความสะดวกต่างๆ แนวทางการพัฒนาพื้นที่สวนสาธารณะในอนาคต จึงได้แก่ 1) การเพิ่มเติมพื้นที่สวนสาธารณะจากการปรับปรุงพื้นที่รกร้างหรือแหล่งเสื่อมโทรม 2) การปรับปรุงและดูแลสวนสาธารณะที่มีอยู่เดิมอย่างสม่ำเสมอ และ 3) การออกมาตรการเชิงนโยบายหรือข้อบังคับเกี่ยวกับพื้นที่สวนสาธารณะ คำสำคัญ: แนวทางการพัฒนา สวนสาธารณะ เขตสายไหม Abstract The objectives of this research are: a) to study the current situation of public parks in Sai Mai district; b) to construct a database of public parks in the district; c) to analyze the public opinions towards the development of parks; and d) to suggest the development guidelines for public parks in line with the needs of the residents in the district. The results of this research show that in Sai Mai district there are two kinds of parks; community park and village park. The per capita park area is 3 square meters per person. Moreover, in terms of public opinion towards the park, most of the respondents highly favor turning abandoned areas into parks, maintaining and improving the existing parks on a regular basis, and increasing the facilities in the parks. Guidelines for developing public parks in the future should focus on a) increasing park areas by revitalizing the abandoned areas, b) restoring and looking after the existing parks on a regular basis, c) issuing policy or restrictions on the park areas. Key words: Guidelines to Develop Public Park Areas Sai Mai District